ISOLED 2015 SHEDS LIGHT TO FUTURE LIGHTING SOLUTIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 15 December 2015 The “International Symposium on LED and OLED Technology in Conjunction with the International Year of Light 2015 (ISOLED 2015)” was held in Universiti Sains Malaysia (USM) organised by the Centre for Research Initiatives (CRI), Natural Sciences USM in collaboration with the Lighting Research Center, Rensselaer Polytechnic Institute (RPI), USA.